(untitled) (Proceedings of International Conference on Special Education, 2017)
The purpose of this study is to compare the effectiveness of Braille writing with slate and stylus the conventional method and the A-J+3+6 method. The authors conducted an experimental study at the cluster primary school for the blind; eighteen blind and visually impaired (BVI) students from Year 2 and Year 3. Ten blind students and eight low vision students were selected as samples. A modified method of braille writing using slate and stylus derived from the abkl method and Mangold method namely A-J+3+6 method was used in this mix-method study. The qualitative data of focus group interview and observations were used to support the quantitative findings. Data analysis showed that method A-J+3+6 (M=76.11 SD=17.81) is more effective in braille writing using slate and stylus rather than the conventional method (M=46.67, SD=24.6) is statistically significant at the 0.05 level (t=2.907, p<0.05). Data also showed that students who used the conventional method tend to do more mirror errors than students who used the A-J+3+6 method (t=1.889, p<0.05). Meanwhile, study also found that there is no statistically significant in braille writing with slate and stylus between the visual acuity; low vision students (M=66.88, SD=26.98) mastered the braille writing skills using slate and stylus better than blind students (M=57.0, SD=25.29) is not statistically significant at the 0.05 level (t=-0.799, p>0.05). Data also showed that there is no statistically significant in mastering the braille writing skills using slate and stylus between the age of onset; students with congenitally blind (M=60.42, SD=27.91) and students with adventitiously blind (M=63.33, SD=23.17) is not statistically significant at the 0.05 level (t=-0.220, p>0.05). Braille Writing; Slate and Stylus; Blind and Visually Impaired